An Analysis Of The Use Of Speech Act Of RequestIn New Moon Movie Manuscripts And Its Subtitling(Socio-Pragmatics Approach) - SURYANI, LILIS (2012)
This research paper is aimed to describe the variation of language form, describe the intention of speech act of request utterance, and describe the equivalence of the politeness pattern on speech act of request utterance in New Moon movie and its subtitling. In collecting the data, the writer used documentation and observation method. The data are in the form of word, phrase and sentence which are used to proposed of speech act of request utterance and its subtitling. To clarify the form of speech act of request and its subtitling, the writer refers to linguistic form theory. To describe the intention of speech act of request utterance and its subtitling, the writer refers to speech act theory especially locut ion, illocution and perlocution. To clarify the politeness strategy of speech act of request and its subtitling, the writer employs four types of politeness strategy by Brown and Levinson. Having analyzed the data, the writer finds that the forms of speech act of request and its subtitling are 2 data or 6% word is subtitled into word, 9 data or 29% phrase is subtitled into word, 3 data or 10% phrase is subtitled into phrase, 4 data or 13% positive sentence is subtitled into positive sentence, 1 data or 3% negative sentence is subtitled into negative sentence, 3 data or 10% interrogative sentence is subtitled into interrogative, and 9 data or 29% imperative sentence is subtitled into imperative sentence. The intention of speech act of request and its subtitling are 16 data or 52% request for action, 1 data or 3% request for permission, 5 data or 16% request for offer, 4 data or 13% request for invitation and 5 data or 16% request for proposal. The politeness strategy use on speech act of request utterance and its subtitling are 24 data or 77% bald on record, 3 data or 10% positive politeness, 3 data or 10% negative politeness and 1 data or 3% off record in the form of equivalent and non equivalent. Keyword: subtitling, speech act of request, linguistic